2020
DOI: 10.29333/iji.2020.1328a
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Critical Thinking Techniques on Understanding Reading Skills for Early Grade Students in Elementary School

Abstract: This study aims to determine the effect of reading and critical thinking techniques on students' reading comprehension skills. This study uses quantitative research methods with experimental methods with treatment with a 2 x 2 level design with 40 samples. The data used analysis variance and continued with Tukey and Least Square Differences (LSD) tests. The results showed that: (1) reading comprehension skills of students who learn to use reading techniques Directed Reading Thinking Activity is higher than stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
0
15
0
3
Order By: Relevance
“…In concordance with a recent study [13], the issues of time management, technology, parents, balancing home and teaching, and lack of resources were reflected in the current concerns of these groups of teachers. Another recent study [36] also indicated that early year teachers have transferable interdisciplinary skills that are valued in many private sectors, such as group training and human resources. In line with social cognitive career and motivation theory [14][15][16], these groups of highly skilled participants tended to work in the private sector due to financial considerations.…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with a recent study [13], the issues of time management, technology, parents, balancing home and teaching, and lack of resources were reflected in the current concerns of these groups of teachers. Another recent study [36] also indicated that early year teachers have transferable interdisciplinary skills that are valued in many private sectors, such as group training and human resources. In line with social cognitive career and motivation theory [14][15][16], these groups of highly skilled participants tended to work in the private sector due to financial considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of DRTA has proven to be effective in improving students' reading comprehension, learning motivation, and learning achievement (Erliana, 2011;Maisarah, 2018;Setiartin, 2018). Students who were treated by DRTA showed a better understanding of a reading text and able to make predictions related to the contents of the text (Ardhian et al, 2020). Moreover, DRTA could improve students' reading comprehension and ethical awareness; it allows students to practice their reading skills, go through thinking processes, guess the content of unfamiliar texts, and connect their knowledge and experience to reading (Chaemsai & Rattanavich, 2016).…”
Section: Discussion Directed Reading -Thinking Activity (Drta)mentioning
confidence: 99%
“…Sixth, multicultural education provides hope in overcoming various societal turmoil that has occurred recently. Seventh, multicultural education has human, social, and spiritual values (Ardhian et al, 2020;Rachmadtullah et al, 2020;Syahputra, 2020).…”
Section: Multicultural Education Based On Local Cultural Valuesmentioning
confidence: 99%